Texture and microstructure improvement of hot-deformed magnets with platelet-like nano h-BN addition. (15th July 2018) - Li, Ming; Chen, Renjie; Jin, Chaoxiang; Yu, Jinhong; Tang, Xu; Chen, Guoxin; Sun, Jie; Wang, Zexuan; Yan, Aru
Abstract: The microstructure of ribbons interface was optimized by doping the hexagonal boron nitride nanoplatelets (h-BNNP) in hot-deformed magnets. The remanence increased markedly and reached to a maximum value of 14.06 kGs. The coercivity and the energy product exhibited similar variation trends to the remanence, showing maxima of 16.92 kOe and 49 MGOe, respectively. Microscopy observations revealed that surface grains of ribbons tended to align with the interior grains due to the uniform local compressive stress induced by h-BNNP with relatively large flat surface, resulting in hot-deformed magnets with microscopically homogeneous structure and improved texture. Graphical abstract: Unlabelled Image